2022
DOI: 10.4236/aa.2022.123011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Women’s Status on Consanguinity in the Arab Society of Israel

Abstract: Background: Consanguinity is a traditional phenomenon that is common in many communities worldwide. In Arab countries, its prevalence is considered to be high, despite its decrease in some Arab societies. According to the Arab society in Israel, the rates of consanguineous marriages (CMs) recently were found to be increasing in the last decade. Generally, various socio-demographic factors play an important role in determining the prevalence rates of consanguineous marriages. Objective: The purpose of the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Most of the studies that examined this relation demonstrated that consanguinity associated with less educated participants in Turkey, India, and Jordan [42,39,43] and locally in Israel [44,45]. On the other hand, some studies found contradicting results for example in Saudi Arabia, where there is still a high prevalence of CMs despite increased educational level, this may be attributed to the fact that this practice is more influenced by attitude towards this type of marriage rather than educational level [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies that examined this relation demonstrated that consanguinity associated with less educated participants in Turkey, India, and Jordan [42,39,43] and locally in Israel [44,45]. On the other hand, some studies found contradicting results for example in Saudi Arabia, where there is still a high prevalence of CMs despite increased educational level, this may be attributed to the fact that this practice is more influenced by attitude towards this type of marriage rather than educational level [19].…”
Section: Discussionmentioning
confidence: 99%